PERLINDUNGAN HUKUM DARI KEKERASAN DALAM RUMAH TANGGA MENURUT UU NOMOR 23 TAHUN 2004 - L. Elly AM Pandiangan (Fakultas Hukum Universitas Kristen Indonesia, 2017)
Abstract The Violence in Family often too difficult to detect and the public paradigm still assume that stuff is internal affairs of the families concerned, the presence of Laws number 23 years 2004 about the elimination of the violence at home, is expected to provide protection for the citizen of the state from the unconfortable sense and as forms of the violence however number of the violence at home in everyday instantly increase. As the Writer will explore how does the role of Laws number 23 years 2004 about exlusion of the violence at home in giving guarantee protections for the citizen of the state especially for them which is a victims of the violence that happened at home. By the question which focused on: Whether it has enough to protect the citizen of the state that being a victim of violence a Home?, and How should be done for decreasing of the number violence case at home that happened in Indonesia? The conclusion that founded by the writer that is principle Laws number 23 years 2004 about removal of the Violence at Home has been enough to provide the protection to the victims and the elementary to the law enforcement. But in its implementation must be done in a way of comprehence and sistematic, not only with the country through the tools of its power and also with the public that supporting the deletion of the violence at Home. Keywords: Perlindungan hukum dari kekerasan dalam rumah tangga